Managing social challenges in the nuclear decommissioning industry: A responsible approach towards better performance. Issue 7 (October 2017) - Invernizzi, Diletta Colette; Locatelli, Giorgio; Brookes, Naomi J.
Abstract: At the end of their lifecycle, several large infrastructure will have to be dismantled, presenting unfamiliar challenges. Therefore, project management will need to focus extensively on the delivery of successful decommissioning projects to meet stakeholders' expectations and funding constraints. While there is an extensive literature that investigates the techno-economic aspects of decommissioning, social aspects remain remarkably under-investigated. Even if stakeholder communication, involvement and engagement are widely believed to be key enablers for the success of a project, often the needs and preferences of local communities are neglected and a participatory-based form of dialogue averted. Consequently, decommissioning projects fail to meet their intended objectives. Focusing on the nuclear decommissioning industry, this paper addresses the literature gap concerning social responsibility. A deductive method to formulate and validate theories regarding the social challenges for decommissioning is developed through a review and analysis of salient case studies. Highlights: Project management knowledge in construction is far greater than decommissioning. Decommissioning projects have to be managed in a socially-responsible way. Nuclear decommissioning projects are complex, long, risky and expensive. This paper presents a socio-economic review of nuclear decommissioning projects. Timely engagement, early planning and siting results to be key success factors.